2019
DOI: 10.3390/agronomy9120787
|View full text |Cite
|
Sign up to set email alerts
|

Visual Symptoms, Vegetative Growth, and Mineral Concentration in Fig Tree (Ficus carica L.) Under Macronutrient Deficiencies

Abstract: The common fig is an edible fruit which is appreciated for its organoleptic characteristics and high commercial value. Several factors, including mineral nutrition, affect fig production. Macronutrients fulfill specific functions in the metabolism of plants, affecting some functions when they are at low levels. So, in the present investigation, the visual symptoms of nitrogen, phosphorus, potassium, calcium, and magnesium deficiencies were identified and characterized, as well as their effects on vegetative gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…The aforementioned effects are explained because the plant tends to balance ionic charges inside the cells, so that, as there is a low concentration of K + and Ca ++ ions, a greater accumulation of Fe ++ , Mn ++ ions occurs, Zn ++ and Cu ++ , all of them cations, as well as K + and Ca ++ (Mengel et al, 2001). Results found in the present investigation coincide with those reported by Garza-Alonso et al (2019), where similarities were observed in the behavior of minerals in the tissues of the fig tree in the absence of macronutrients.…”
Section: Concentration Of Minerals In Fruitsupporting
confidence: 91%
See 1 more Smart Citation
“…The aforementioned effects are explained because the plant tends to balance ionic charges inside the cells, so that, as there is a low concentration of K + and Ca ++ ions, a greater accumulation of Fe ++ , Mn ++ ions occurs, Zn ++ and Cu ++ , all of them cations, as well as K + and Ca ++ (Mengel et al, 2001). Results found in the present investigation coincide with those reported by Garza-Alonso et al (2019), where similarities were observed in the behavior of minerals in the tissues of the fig tree in the absence of macronutrients.…”
Section: Concentration Of Minerals In Fruitsupporting
confidence: 91%
“…For the fig tree, Garza-Alonso et al (2019) reported the effects of deficiency of N, P, K, Ca, and Mg on the vegetative growth and minerals concentration in leaf, root, and stem; however, few studies have been conducted on the effects of macronutrient deficiencies in the quality of fig fruits. Esref et al (2008) studied the effects of different doses of Ca, where the average fruit weight decreased from 16.24 to 14.43 g when this element was not applied, which also produced a 34% reduction in yield per plant.…”
Section: Introductionmentioning
confidence: 99%
“…In our current work, we confirmed that a concentration of 100 mM NaCl was well tolerated for four weeks since proline concentration, shoot, and fruit growth were similar to those of controls. Moreover, mineral elements in the control plant are in line with data measured in fig fruit [36] and other fig organs [37]. On the other hand, Na + was massively accumulated in the root tissue and increased in all organs but not in the leaf.…”
Section: Discussionsupporting
confidence: 86%
“…As illustrated in Table 4, there exist substantial to notably significant correlations between metrics of plant height and stem diameter in relation to these macronutrients, with the correlation coefficients (r) delineating total N=0.88**, available P=0.69*, exchangeable K=0.85**, and again for available P=0.78** and exchangeable K=0.88**. The vegetative growth of plants (plant height and stem diameter) is influenced by the high Nitrogen content (Garza-Alonso et al, 2019;Longnecker, 2021) as Nitrogen functions to increase leaf quantity and area, thereby affecting photosynthesis (Chang et al, 2020;Croft et al, 2017;Ren et al, 2018). Phosphorus plays a role in protein synthesis and cell division, promoting tissue development (Saleem et al, 2020;Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%